Family atmosphere and its effects on the adolescents deviant behaviour - Yahaya, Azizi; Abd. Ghaffar, Mohd. Najib; Baharom, Badrulzaman (2010)
This study is aimed at identifying correlations between family atmosphere and deviant behavior among adolescents in the Pontian District, Johor. A total of 210 students from a few secondary schools in the Pontian District were chosen as respondents for this study. Descriptive statistics of frequency and mean were used for distribution analysis, whereas inference statistics which is Pearson correlation were used for analyzing relations between family atmosphere and juvenile behavior. Analysis of the results shows a significant relation between parents behavior traits and juvenile deviant behavior.